The name change process and gender identity recognition: proposals for judicial and legislative reform - Fernández Espinoza, William Homer (2021)
This research work studies the process of changing the name and sex of LGTBIQ people (acronym formed by the initials of the words lesbian, gay, transsexual, bisexual, intersexual, and queer), who have historically been discriminated against and violated in their human rights of access to justice and recognition of legal personality concerning their sexual orientation and gender identity. For its development, doctrine, legislation, and jurisprudence were analyzed to propose a judicial and legislative reform that establishes the parameters for the integral adequacy of self-perceived gender identity.